Pengaruh Investasi Berkelanjutan (ESG), Corporate Governance, dan Struktur Modal Terhadap Nilai Perusahaan Perbankan yang Terdaftar di BEI Tahun 2021-2024 - Annisa Nurul Pebriyanti; Azzahra Najwa Debby M; Salwa Toha; Dewi Nur Azizah; Anastasia Putri; Amellia Agustin W; Maria Yovita R. Pandin (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
The purpose of this study is to examine the impact of capital structure, corporate governance (CG), and sustainable investment (environmental, social, and governance/ESG) on firm value in the banking industry listed on the Indonesia Stock Exchange (IDX) between 2021 and 2024. The Partial Least Squares–Structural Equation Modeling (PLS-SEM) method is the quantitative approach used in this study. SmartPLS software is used to analyze secondary data collected from corporate governance disclosures, sustainability reports, and annual financial reports. The results show that corporate governance has a significant and positive impact on business value, while sustainable investment (ESG) has a negative but negligible effect. On the other hand, capital structure has a substantial and detrimental impact on firm value. ESG, corporate governance, and capital structure all have a significant simultaneous impact on firm value; their coefficient of determination (R2) is 0.584, meaning that these three factors explain 58.4% of the variation in firm value. These results imply that while excessive use of debt tends to lower company value, sound corporate governance is the main determinant in increasing firm value in the banking industry. However, the application of ESG principles has not yet shown a substantial impact on market value, suggesting that investors in Indonesia's banking industry do not completely take sustainability factors into account. In order to increase company value and business competitiveness in the capital market, this study highlights the significance of synergy between solid financial practices, excellent corporate governance, and a dedication to sustainability